Phenotypic and genotypic characterization of vibrio cholerae from seafood and environmental sources in Sarawak - Lai, Lee San (Universiti Malaysia Sarawak (UNIMAS), 2006)
In this study, a total of 152 surface water samples from 7 different rivers and 144 seafood samples (shrimps and cockles) marketed in the Kuching-Samarahan District, Sarawak were investigated for the presence of V. cholerae. Samples were collected monthly for a period of 8 months from December, 2003 to July, 2004. Identification of the bacterium was done by both morphological and biochemical tests. A molecular tool for species-specific identification by targeting the outer membrane protein (ompW) gene was then applied in this study to confirm the identity of the V. cholerae isolates. The results showed that 24 (15.8%) of the surface water samples and I (0.007%) of the seafood sample were positive for V. cholerae. The results revealed a moderate and low occurrence of V. cholerae in water sample and seafood respectively. Multiple presumptive colonies were taken from TCBS agar for further identification. Based on the presence of the ompW gene, 54 isolates were confrrmed as V. cholerae bacteria. Serological agglutination test revealed that all of the 54 confirmed V. cholerae isolates belonged to non-agglutinating V. cholerae species or V. cholerae non-01. The V. cholerae isolates were further studied to determine their antibiotic resistance, the occurrences of plasmids, DNA fingerprinting using RAPD-PCR, ERIC-PCR and BOX-PCR fmgerprinting and the presence of the ace, ctxA, ctxB and zot genes. Antibiotic susceptibility test showed that the isolates exhibited high resistance towards bacitracin (98%), streptomycin (96%), erythromycin (91 %) and methicillin (82%). The isolates also demonstrated various degrees of resistance toward other antibiotics and antimicrobial agents used such as carbenicillin (22%), ampicillin and trimethoprim-sulfamethoxazole (Sxt) (13%) and nalidixic acid (4%). All isolates were, however, susceptible to tetracycline, gentamycin and chloramphenicol. Plasmid profile analysis showed the presence of one or more plasmids in 42 (77.8%) isolates with sizes ranging from 3.7 kb to 57.5 kb. Overall, 13 distinctive plasmid profiles were generated. There was no correlation between the plasmid profiles and the antimicrobial resistance patterns. The molecular diversity of the 54 V. cholerae isolates were later investigated by randomly amplified polymorphic DNA (RAPD)-PCR analysis, enterobacterial repetitive intergenic consensus (ERIC)-PCR analysis and BOX-PCR analysis. RAPD-PCR, ERIC-PCR and BOX-PCR successfully amplified polymorphic DNA fragments in all the 54 V. cholerae isolates tested which resulted in 39, 43 and 38 distinct fmgerprints respectively.